Azacytidine Treatment Inhibits the Progression of Herpes Stromal Keratitis by Enhancing Regulatory T Cell Function - Varanasi, Siva Karthik (J Virol, 2017)
Ocular infection with herpes simplex virus 1 (HSV-1) sets off an inflammatory reaction in the cornea which leads to both virus clearance and chronic lesions that are orchestrated by CD4 T cells. Approaches that enhance the function of regulatory T cells (Treg) and dampen effector T cells can be effective to limit stromal keratitis (SK) lesion severity. In this report, we explore the novel approach of inhibiting DNA methyltransferase activity using 5-azacytidine (Aza; a cytosine analog) to limit HSV-1-induced ocular lesions. We show that therapy begun after infection when virus was no longer actively replicating resulted in a pronounced reduction in lesion severity, with markedly diminished numbers of T cells and nonlymphoid inflammatory cells, along with reduced cytokine mediators. The remaining inflammatory reactions had a change in the ratio of CD4 Foxp3(+) Treg to effector Th1 CD4 T cells in ocular lesions and lymphoid tissues, with Treg becoming predominant over the effectors. In addition, compared to those from control mice, Treg from Aza-treated mice showed more suppressor activity in vitro and expressed higher levels of activation molecules. Additionally, cells induced in vitro in the presence of Aza showed epigenetic differences in the Treg-specific demethylated region (TSDR) of Foxp3 and were more stable when exposed to inflammatory cytokines. Our results show that therapy with Aza is an effective means of controlling a virus-induced inflammatory reaction and may act mainly by the effects on Treg. IMPORTANCE HSV-1 infection has been shown to initiate an inflammatory reaction in the cornea that leads to tissue damage and loss of vision. The inflammatory reaction is orchestrated by gamma interferon (IFN-γ)-secreting Th1 cells, and regulatory T cells play a protective role. Hence, novel therapeutics that can rebalance the ratio of regulatory T cells to effectors are a relevant issue. This study opens up a new avenue in treating HSV-induced SK lesions by increasing the stability and function of regulatory T cells using the DNA methyltransferase inhibitor 5-azacytidine (Aza). Aza increased the function of regulatory T cells, leading to enhanced suppressive activity and diminished lesions. Hence, therapy with Aza, which acts mainly by its effects on Treg, can be an effective means to control virus-induced inflammatory lesions.